Sesquiterpenes and sesquiterpenoids harbor modulatory allosteric potential and affect inhibitory GABA(A) receptor function in vitro - Janzen, Dieter; Slavik, Benedikt; Zehe, Markus; Sotriffer, Christoph; Loos, Helene; Büttner, Andrea; Villmann, Carmen (Journal of Neurochemistry, 2021)
Naturally occurring compounds such as sesquiterpenes and sesquiterpenoids (SQTs) have been shown to modulate GABA(A) receptors (GABA(A)Rs). In this study, the modulatory potential of 11 SQTs at GABA(A)Rs was analyzed to characterize their potential neurotropic activity. Transfected HEK293 cells and primary hippocampal neurons were functionally investigated using electrophysiological whole-cell recordings. Significantly different effects of beta-caryophyllene and alpha-humulene, as well as their respective derivatives beta-caryolanol and humulol, were observed in the HEK293 cell system. In neurons, the concomitant presence of phasic and tonic GABA(A)R configurations accounts for differences in receptor modulation by SQTs. The in vivo presence of the gamma(2) and delta subunits is important for SQT modulation. While phasic GABA(A) receptors in hippocampal neurons exhibited significantly altered GABA-evoked current amplitudes in the presence of humulol and guaiol, negative allosteric potential at recombinantly expressed alpha(1)beta(2)gamma(2) receptors was only verified for humolol. Modeling and docking studies provided support for the binding of SQTs to the neurosteroid-binding site of the GABA(A)R localized between transmembrane segments 1 and 3 at the ((+)alpha)-((-)alpha) interface. In sum, differences in the modulation of GABA(A)R isoforms between SQTs were identified. Another finding is that our results provide an indication that nutritional digestion affects the neurotropic potential of natural compounds.
CRIS-Team WoS Importer:2021-08-13